Descripción de los estados inmaduros de Phyllophaga (Phytalus) totoreana y Phyllophaga (Phyllophaga) opaca del norte de Sinaloa, México - Cuate-Mozo, Víctor Alfonso; Aragón-García, Agustín; Lugo-García, Gabriel Antonio; Reyes Olivas, Álvaro; Aragón-Sánchez, Miguel; Pérez-Torres, Betzabeth Cecilia (Instituto de Ecología, A.C., 2020)
The descriptions of third stage larvae of Phyllophaga (Phytalus) totoreana Morón and Phyllophaga (Phyllophaga) opaca Moser with collected specimens associated with the roots of Pennisetum sp. (Poaceae) and the farming of corn (Zea mays L.) (Poaceae) established between 118-119 m altitude in the municipality of Fuerte, Sinaloa, Mexico. The pictures of diagnostic characters, comments on similarities with larvae of other species and a taxonomic a key to the larvae of Mexico genera of Phyllophaga is included.